Indumentária funcional para missionários não religiosos internacionais - Oliveira, Rodrigo Augusto Udenal de (2014)
Missionary service volunteering basically characterized by the attitude of giving a specific cause or purpose of the common good. This act requires considerable dedication of the individual who performs therefore motivation without financial basis is essential. Moreover, it is necessary to meet the needs for each operation, and the dress is a key factor with regard to the adequacy of the missionary adhered to the cause. It is noticed that the garment has significant role in the way of exercising voluntary work and can improve the conditions of international non-religious missionaries in different parts of the world. For this, we need to master concepts of symbolism regarding clothes and also concepts of symbolic and functional aspects related to them so that the pieces of the workers are perfectly suited to its function. To develop these products, a system design is essential, for only then is it possible to achieve positive results for the proposed functional design. In order to put into practice the theoretical foundations, the methodology of this study will adopt an exploratory field research conducted through a questionnaire in which progressive issues have arranged from simple to more complex clear and objective language and the reading of this approach will be accurate and faithful to the responses noted by respondents.